(untitled) (Journal of Imam Al-Kadhim College, 2023)
The research tagged "The facilitator of purity when earthquakes occur - a jurisprudential study -" dealt with the statement of the facilitated provisions of the sayings of jurists when earthquakes occur And highlights the importance of the subject in the human need to facilitate in purity if earthquakes occur, has come Sharia easy and lift the embarrassment of the taxpayers Vardna in our research to show the extent of the breadth of Sharia and tolerance and take the easiest of the sayings of jurists to lift the embarrassment of the taxpayer, has required the nature of the research on the introduction and two sections and conclusion The introduction has included the importance of the subject and its causes, and the first section has included a statement of the concept of earthquake and its causes and related words, and the second section has included a statement of issues related to purity when the earthquake occurs, and the conclusion has deposited a summary of its findings .